Microencapsulation Improved Fumaric Acid and Thymol Effects on Broiler Chickens Challenged With a Short-Term Fasting Period - Abdelli, Nedra; Francisco Pérez, José; Vilarrasa, Ester; Melo-Duran, Diego; Cabeza Luna, Irene; Karimirad, Razzagh; Solà-Oriol, David (Frontiers in Veterinary Science, 2021)
The first objective of this study was to demonstrate the usefulness of the microencapsulation technique to protect fumaric acid and thymol, avoiding their early absorption and ensuring their slow release throughout the gastrointestinal tract (GIT). For this purpose, the release of a lipid matrix microencapsulated brilliant blue (BB) was assessed in vitro, using a simulated broiler intestinal fluid, and in vivo. In vitro results showed that more than 60% of BB color reached the lower intestine, including 26.6% and 29.7% in the jejunum and ileum, respectively. Another objective was to study the effect of microencapsulated fumaric acid, thymol and their mixture on the performance and gut health of broilers challenged with a short–term fasting period (FP). One-day-old male ROSS 308 chickens (n=280) were randomly distributed into 7 treatments, with 10 replicates of 4 birds each. Dietary treatments consisted of a basal diet as negative control (NC), which was then supplemented by either non-microencapsulated fumaric acid (0.9g/kg), thymol (0.6g/kg), or a mixture of them. The same additive doses were also administered in a microencapsulated form (1.5g/kg and 3g/kg for the acid and thymol, respectively). At day 21, chickens were subjected to a 16.5 h short-term FP to induce an increase in intestinal permeability. Growth performance was assessed weekly. At day 35, ileal tissue and cecal content were collected from one bird per replicate to analyze intestinal histomorphology and microbiota, respectively. No treatment effect was observed on growth performance from day1-21, before the short-term FP challenge (P > 0.05). Microencapsulated fumaric acid, thymol, or their mixture improved the overall G:F (gain-to-feed ratio) and increased ileal villi height to crypt depth ratio (VH:CD) (P < 0.001). Microencapsulated thymol improved the feed efficiency (P < 0.001) and economic margins over feed costs. The microencapsulated mixture of fumaric acid and thymol increased cecal abundance of Ruminococcaceae, Lachnospiraceae and Peptostreptococcaceae, while decreasing that of Rikenellaceae and Enterobacteriaceae. In conclusion, microencapsulation improved fumaric acid and thymol effects on fasted broiler chickens.